PERAN WANITA DALAM MENGAJARKAN PENDIDIKAN AGAMA ISLAM DI ERA MODERN - Silvia Andine; Selamet (As-Sulthan Journal of Education, 2025)
This study aims to analyze the role of women in teaching Islamic Religious Education in the modern era through family, formal and non-formal education, and digital media. The research applied a qualitative method with a library research approach by reviewing relevant literature and scientific articles. The findings reveal that women serve as the first madrasa in the family, as educators in institutions, and as preachers through digital platforms. Despite challenges such as dual roles, patriarchal culture, limited digital literacy, and lack of social support, women still play a significant role in strengthening Islamic education. This study emphasizes the importance of empowering women through digital literacy, family and community support, and Islamic organizations to ensure adaptive education aligned with Islamic values